Analisis Keseimbangan Operasional Proses Kalibrasi Menggunakan Metode Line Balancing: (Studi Kasus: PT Pal Indonesia) - Rafi Danendra Adiatma; Yekti Condro Winorsito (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Company PT. PAL Indonesia is a manufacturer of Indonesian Defence system equipment which is especially in the largest marine sector in Indonesia. In addition, PT. PAL Indonesia has 22 divisions. One of them is the Technology & Quality Assurance Division. One element that requires precise and accurate measurement is calibration. In the operational balance the calibration process is the key to overcoming the calibration request in the department. This research uses the line balancing method to determine the process time from the beginning to the end of the calibration process. The results obtained from the balance delay method are line balancing methods, in the previous company condition of 77% and after the improvement has been reduced to 5%, it can be concluded that the balance delay has decreased so that the performance is better. Meanwhile, in the Smoothness Index, the results that are known in the company's previous condition are 9 minutes and the results obtained after the repair are 3 minutes with the position weight method (Ranked Positional Weight) getting the late operation speed is 160 minutes so that it is used as a cycle time in the calculation of this method in the process of knowing the calibration work from the beginning to the end.